THE DIAGNOSIS OF HYPOTHYROIDISM - Nabiyeva F. S.; Yakubova D. M.; Abdualimova L. A. (Web of Journals Publishing, 2025)
Hypothyroidism is the result of inadequate production of thyroid hormone or inadequate action of thyroid hormone in target tissues. According to some epidemiological studies, the prevalence of manifest primary hypothyroidism in the population is 0.2-2.0%, subclinical - up to 10% in women and up to 3% in men. Hypothyroidism is most common among older women, where the prevalence rate reaches 12%. The wide array of symptoms of hypothyroidism indicates an effect on metabolism and dysfunction in multiple organ systems.
Keywords: Hypothyroidism, thyroid gland, etiology, pathogenesis, clinical symptoms, diagnostics.